Microsurgical Resection of Brainstem Arteriovenous Malformation: 2-Dimensional Operative Video. Issue 2 (23rd November 2019) - Hendricks, Benjamin K; Spetzler, Robert F
Abstract: Brainstem arteriovenous malformations (AVMs) are rare lesions (2%-6% of all intracranial AVMs) that are surgically challenging because of the high eloquence of the brainstem, including dense fiber tracts, cranial nerves, and multiple vital cerebrovascular structures. All these lesions possess eloquence and deep venous drainage, making them innately Spetlzer–Martin grade III or above. This patient had a large midbrain AVM with a complex clinical course beginning with ventriculoperitoneal shunting due to mass effect; the patient experienced 4 hemorrhages, underwent radiation treatment, and finally underwent surgical resection. The surgical approach involved a large torcular craniotomy exposing all posterior sinuses at the confluence. The vein of Galen was exposed and carried deeply to permit ambient cistern opening and relaxation of the cerebellum. Because of earlier radiation therapy, the vessels had undergone hyalinosis, which resulted in difficult manipulation of the nidus but did permit excellent coagulation of the vessels. The complete nidus was removed, as confirmed on postoperative angiography. The patient gave informed consent for surgery and video recording. Institutional review board approval was deemed unnecessary. Used with permission from Barrow Neurological Institute, Phoenix, Arizona.